Multiple Sclerosis and the Risk of Cardiovascular Diseases: A Mendelian Randomization Study - Yang, Fangkun; Hu, Teng; He, Kewan; Ying, Jiajun; Cui, Hanbin (Frontiers in Immunology, 2022)
Background Observational studies suggested that multiple sclerosis (MS) is associated with cardiovascular diseases (CVDs). However, the causal association has not been fully elucidated. Thus, we aim to assess the causality of the associations of MS with risk of CVDs. Methods A two-sample Mendelian randomization (MR) study was performed to explore the causality. Genetic instruments were identified for MS from a genome-wide association study (GWAS) involving 115,803 individuals. Summary-level data for CVDs were obtained from different GWAS meta-analysis studies. MR analysis was conducted mainly using the inverse-variance weighted (IVW) method. Sensitivity analyses were further performed to ensure the robustness of the results. Results This MR study found suggestive evidence that genetic liability to MS was associated with an increased risk of coronary artery disease (CAD) [odds ratio (OR), 1.02; 95% confidence interval (CI), 1.00–1.04; p = 0.03], myocardial infarction (MI) (OR, 1.03; 95% CI, 1.00–1.06; p = 0.01), heart failure (HF) (OR, 1.02; 95% CI, 1.00–1.04; p = 0.02), all-cause stroke (AS) (OR, 1.02; 95% CI, 1.00–1.05; p = 0.02), and any ischemic stroke (AIS) (OR, 1.02; 95% CI, 1.00–1.05; p = 0.04). The null-association was observed between MS and the other CVDs. Further analyses found little evidence of pleiotropy. Conclusions We provided suggestive genetic evidence for the causal associations of MS with increased risk of CAD, MI, HF, AS, and AIS, which highlighted the significance of active monitoring and prevention of cardiovascular risk to combat cardiovascular comorbidities in MS patients.